The development experience of Malaysia : Lessons for Africa in general and Nigeria in particular - Ajibewa, Aderemi Isola (Universiti Malaysia Sarawak (UNIMAS), 1997)
The economic miracles of Malaysia and other South-East Asian states and the possibility of applying them outside the region is much talked, but little has been done, practically at least until recently. The Malaysian economy has registered impressive growth due to global trade connection, peaceful regional climate, investment linkage, as well as lessons learnt from the experiences of the Asian "tigers," Hong Kong, Taiwan, Singapore and South Korea.